Applications of Haptic Technology, Virtual Reality, and Artificial Intelligence in Medical Training During the COVID-19 Pandemic - Motaharifar, Mohammad; Norouzzadeh, Alireza; Abdi, Parisa; Iranfar, Arash; Lotfi, Faraz; Moshiri, Behzad; Lashay, Alireza; Mohammadi, Seyed Farzad; Taghirad, Hamid D. (Frontiers in Robotics and AI, 2021)
This paper examines how haptic technology, virtual reality, and artificial intelligence reduce the physical contact in medical training during the COVID-19 Pandemic. Notably, any mistake made by the trainees during the education stages might lead to undesired complications for the patient. Therefore, training of the medical skills to the trainees have always been a challenging issue for the expert surgeons, and this is even more challenging in pandemics. The current method of surgery training needs the novice surgeons to attend some courses, watch some procedure, and conduct their initial operations under the direct supervision of an expert surgeon. Owing to the requirement of physical contact in this method of medical training, the involved people including the novice and expert surgeons confront a potential risk of infection to the virus. This survey paper reviews novel recent breakthroughs along with new areas in which assistive technologies might provide a viable solution to reduce the physical contact in the medical institutes during the COVID-19 pandemic and similar crises.